Genotyp-Phänotyp-Korrelationen bei Kindern und Jugendlichen mit nichtklassischem adrenogenitalen Syndrom mit 21-Hydroxylase-Defekt - Dörr, Helmuth-Günther; Schulze, Nadja; Bettendorf, M.; Binder, G.; Bonfig, W.; Denzer, C.; Dunstheimer, D.; Salzgeber, K.; Schmidt, H.; Schwab, K. O.; Voss, E.; Wabitsch, M.; et al. (Monatsschrift Kinderheilkunde, 2020)
Background: Nonclassical congenital adrenal hyperplasia due to 21-hydroxylase deficiency (NCCAH) is caused by mutations in the active 21-hydroxylase gene (CYP21A2). The clinical symptoms can vary greatly. To date, no systematic studies have been undertaken in Germany. Objective: Description of the phenotype, evaluation of the diagnostics, genotype-phenotype correlation. Patients and methodology: Retrospective analysis of the data of 134 patients (age range 0.1–18.6 years) in a multicenter study covering 10 pediatric endocrinology centers in Bavaria and Baden-Württemberg. The data were collected on site from the medical records. In 126 patients 233 alleles with a mutation of the CYP21A2 gene were identified. A genotype-phenotype correlation of the mutation findings was undertaken (C1: severe/mild, C2: mild/mild). Individuals with a heterozygote mutation (C3) were also included in the analysis. The data were collected with the approval of the ethics committee of the University Hospital of Erlangen during the time period of 2014 and 2015. Results (MW ± SD): Out of 134 patients (115 female, 29 male) 117 were symptomatic. The chronological age (CA) at diagnosis was 7.1 ± 4.4 years. The most frequent symptom (73.5%) was premature pubarche. The height-standard deviation score (SDS) on diagnosis was 0.8 ± 1.3 and the body mass index (BMI)-SDS was 0.8 ± 1.2. Bone age (BA) was ascertained in 82.9% of the symptomatic patients. The difference between BA and CA was 1.9 ± 1.4 years. Basal 17-hydroxyprogesterone (17-OHP) concentrations were 14.5 ± 19.1 ng/ml (18 patients <2 ng/ml). In total 58.1% mild and 34.7% severe mutations were found. The most common mutation (39.1%) was p.Val281Leu and 65.8% of the patients could be allocated to group C1. No phenotypical differences were found between the three mutation groups. The 17-OHP levels (basal and after ACTH) in the ACTH test were highest in group C1 and also significantly higher in group C2 than in group C3. The ACTH-stimulated cortisol levels (ng/ml) were significantly lower in groups C1 (192.1 ± 62.5) and C2 (218 ± 50) than in C3 (297.3 ± 98.7). Conclusion: Most of the patients had symptoms of mild androgenization. Male patients were underdiagnosed. The diagnostics were not standardized. Differences between the types of mutations were found in the hormone concentrations but not in the phenotype. We speculate that further, as yet not clearly defined, factors are responsible for the development of the respective phenotypes.
CRIS-Team Scopus Importer:2020-07-24
Keywords: 17-OHP; ACTH stimulation test; Androgenisation; CYP21A2 gene mutations; Premature pubarche